Postpartum pituitary necrosis and hypopituitarism, a sequela of severe falciparum malaria in pregnancy – a case report - Ahmed, Moeez; Shahid Ahmed (Journal of the Pakistan Medical Association, 2025)
A 37 year old woman presented with a history of weakness and lethargy for many years. She had been amenorrhoeic for 5 years after a still birth at 37 weeks gestation, due to severe falciparum malaria. On examination, she appeared pale and lethargic, with a blood pressure of 100/70 mm Hg. Her systemic examination was unremarkable. Laboratory tests revealed low 9.00 am serum ACTH and cortisol levels, along with low free T4, FSH and LH levels. A short synacthen test showed an inadequate cortisol response at 30 minutes. MRI of the Pituitary gland displayed an empty sella. She was diagnosed with hypopituitarism due to postpartum pituitary necrosis, and was treated with hydrocortisone, thyroxine and sex hormone replacement therapy. The patient showed an excellent response to treatment. Keywords: Postpartum, hypopituitarism, falciparum malaria.